Improvement of Methods for Assessing the Shadow Economy in Agricultural Enterprises for the Purpose of Preventing Threats to Food Security - V. I. Avdiyskiy (Финансы: теория и практика, 2025)
The subject of the research is methods for assessing the shadow economy in the field of agricultural production. The purpose of the study is to propose methods for identifying the shadow economy in agricultural enterprises, which negatively affects economic growth and the balanced development of regions and the country as a whole. The objectives of the study were scientific and methodological substantiation of indirect methods for assessing the indicators of the shadow economy in agricultural enterprises; an objective assessment of possible financial losses from unaccounted-for activities; and development of methods for a comprehensive assessment of the shadow economy in the field of agricultural production to timely identify and address the causes and conditions that have a destabilizing effect on the country’s food security. The study used an analytical method to identify cause-and-effect relationships between the studied process of unaccounted-for agricultural production, financial losses and threats to food security. It is concluded that in order to effectively combat the shadow economy in the agricultural sector, it is necessary to improve methods for assessing the level of informal production, which will not only objectively determine the actual state of affairs, but also develop effective measures to eliminate the causes and conditions conducive to the organization of this illegal activity. The scientific novelty of the study is the identification of imbalances between the indicators of financial and economic activity of agricultural enterprises, which indicate signs of unaccounted-for agricultural production. The author proposes to carry out a comprehensive analysis of all indicators of the results of financial and economic activities in this field of production, which allows us to calculate the actual volumes of products produced. It is also proposed to develop special government programs aimed at identifying threats and minimizing the risks of ensuring the stable functioning of agricultural enterprises through the introduction of modern accounting and control technologies. The article offers a comparative analysis of the results of financial and economic activities of the main stages of production and processing of agricultural products, which will reveal the facts of shadow production, calculate the amount of financial losses and promptly eliminate the causes and conditions conducive to shadow production in the agricultural sector.